2008
DOI: 10.1515/cclm.2008.311
|View full text |Cite
|
Sign up to set email alerts
|

Single nucleotide polymorphisms in ABCG5 and ABCG8 genes in Chilean subjects with polygenic hypercholesterolemia and controls

Abstract: Our data showed that the ABCG5 1950C > G polymorphism is associated with HC in the studied population. Nevertheless, this study is limited by its sample size.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 31 publications
1
8
0
Order By: Relevance
“…The frequency of CC homozygous genotype for ABCG5 1950C>G was higher in hypercholesterolemic patients than in controls (42% vs. 10%, P <0.001). On the other hand, no significant differences for the ABCG8 251A>G were observed [54]. Allele frequencies of the ABCG8 D19H, Y54C, T400K, and A632V SNPs in patients with ischemic vascular diseases showed no significant differences compared with controls.…”
Section: Discussionmentioning
confidence: 68%
“…The frequency of CC homozygous genotype for ABCG5 1950C>G was higher in hypercholesterolemic patients than in controls (42% vs. 10%, P <0.001). On the other hand, no significant differences for the ABCG8 251A>G were observed [54]. Allele frequencies of the ABCG8 D19H, Y54C, T400K, and A632V SNPs in patients with ischemic vascular diseases showed no significant differences compared with controls.…”
Section: Discussionmentioning
confidence: 68%
“…In addition, due to their skewed distribution, triglyceride data could not be pooled. Twelve studies reported signifi cant associations with baseline triglyceride levels, which mostly involved the p.T400K polymorphism ( 13,29,33 ); however, this was not consistent throughout all included studies ( 8,11,12,27,(30)(31)(32). Finally, in our analyses, we assumed a dominant genetic model, as most of the included studies presented their data according to this model.…”
Section: Discussionmentioning
confidence: 97%
“…The number of study participants ranged from 26 to 1,046. Five studies were conducted in a population of Caucasians ( 5,7,11,13,27 ), three studies investigated Asian populations ( 8,28,29 ), two studies were conducted in a Hispanic population ( 30 ), and two in a mixed racial population ( 31,32 ). The remaining three studies did not report the ethnicity of the study subjects ( 9,12,33 ).…”
Section: Meta-analysis: Characteristics Of Included Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, a study by Salazar et al 16 found correlation between 45 TMJ polymorphism in the adiponectin (ADI-POQ) gene and CAD in a Chilean population. Another Chilean study conducted by Caamaño et al 17 found an association between ABCG5 1950 > G polymorphism and hypercholesterolemia in that specific population. Likewise, Fujita et al 18 found a significant correlation between the genotypes of A419P variants and the levels of total cholesterol.…”
Section: Resultsmentioning
confidence: 81%